2022
DOI: 10.3390/pathophysiology29030041
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Mechanisms of Autoimmune Diseases and Their Relationship with the Resident Microbiota: Friend or Foe?

Abstract: The use of innovative approaches to elucidate the pathophysiological mechanisms of autoimmune diseases, as well as to further study of the factors which can have either a positive or negative effect on the course of the disease, is essential. In this line, the development of new molecular techniques and the creation of the Human Genome Program have allowed access to many more solutions to the difficulties that exist in the identification and characterization of the microbiome, as well as changes due to various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 195 publications
0
12
0
Order By: Relevance
“…This condition could add value in the prevention, diagnosis and treatment of UUI. Indeed, therapy for UUI which consists of behavioral therapy (special diet avoiding irritants and other), perineal physio-kinesitherapy and pharmacological therapy (using antimuscarinics that act by blocking the involuntary contractility of the detrusor), and the adjuvant role of probiotics/prebiotics would be important [48][49][50][51][52].…”
Section: Urgency Urinary Incontinence (Uui)mentioning
confidence: 99%
“…This condition could add value in the prevention, diagnosis and treatment of UUI. Indeed, therapy for UUI which consists of behavioral therapy (special diet avoiding irritants and other), perineal physio-kinesitherapy and pharmacological therapy (using antimuscarinics that act by blocking the involuntary contractility of the detrusor), and the adjuvant role of probiotics/prebiotics would be important [48][49][50][51][52].…”
Section: Urgency Urinary Incontinence (Uui)mentioning
confidence: 99%
“…Treatment of superantigen-induced toxic shock is still limited. Experimental attempts have been undertaken with immunosuppressants, such as dexamethasone, cyclosporine A and rapamycin with the aim of interrupting T cell proliferation [ 53 , 76 , 77 , 78 , 79 ]. Furthermore, intravenous immunoglobulin and, recently, humanized monoclonal antibodies (MoAbs) to neutralize SEs and TSST-1 have been used [ 80 , 81 , 82 , 83 ].…”
Section: Natural and Biological Products As An Alternative Treatment ...mentioning
confidence: 99%
“…can lead to oral microbiota and/or gut dysbiosis, which can play an important role in the development of some diseases, such as autoimmune diseases like rheumatoid arthritis. Prevotella copri contributes to the development of rheumatoid arthritis, while P. histicola [ 104 , 105 ] suppresses it. Studies have shown that when Bifidobacterium longum and L. helveticus are taken in combination they cause a reduction in cortisol, which affects the gut/brain microbiota axis.…”
Section: Effect Of Probiotics and Prebiotics On The Intestinal Microb...mentioning
confidence: 99%